Immediate breast reconstruction using titanised mesh - P. V. Krivorotko; R. S. Pesotskyy; K. Yu. Zernov; A. A. Bessonov; E. K. Zhiltsova; A. V. Komyakhov; T. T. Tabagua; K. S. Nikolaev; K. Yu. Rychagov; V. G. Ivanov; L. P. Gigolaeva; O. A. Ivanova; et al. (Опухоли женской репродуктивной системы, 2020)
Additional covering of the lower pole with allomaterial or its synthetic analogues during immediate breast reconstruction is being performed at the N. N. Petrov National Medical Research Oncology Center, Ministry of Health of Russia, for last 7 years. Initially, epidermal flap was the only option for lower pole coverage; later acellular dermal matrix was used as part of clinical approbation. Average complication rate ranges from 20–35 % due to blood circulatory (supply) disorders.Since 2018, a titanised mesh been used as an additional coverage of the lower pole in the department of breast tumors. Through coating characteristics and its structure the frequency of fatal complications significally decreased.